SocioCar: a transient social vehicular network. (2015) - Esmaeilyfard, Rasool; Hendessi, Faramarz
The increasing use of vehicles and the heavy traffic emerged in metropolises have both turn to an important part of people's daily routine. This situation could provide a unique opportunity for some kind of social communication among people. However, this social communication has its requirements and constraints. In this paper, we introduce the notion of SocioCar to develop a transient social vehicular network service. This service inspires the users to communicate quickly by reducing social constraints. In this regard, one of the key points in this paper is the idea to adapt the user identity and its role in rapid communication. Furthermore, we integrate our design with a user social classification method using Bayesian Networks with an aim to effectively highlight the desired users and predict users' characteristics. Through this approach, we investigate the social classification model and conduct a user study to probe the usefulness of social network.